Natural experiments: Researching life through art. (1st December 2021) - McNiff, Shaun
Natural experiments are examinations of spontaneous and often transformative acts of nature, including artistic expression. The empirical research produces generalizable outcomes as documented during the worldwide COVID-19 pandemic. This article discusses how the unplanned nature of natural experiments is contrary to the pervasive practice of research in higher education, including the author's personal experience as a research advisor. It is suggested that in the future, art-based natural experiments will enable research to correspond to life processes more fully.